Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2013)
This paper reviews recent developments in financing of the Fund's concessional lending and debt relief. It reports the latest available data including the pledges made thus far in response to the Managing Director's fund-raising requests of August 2009 and February and November 2012 aimed at establishing a self-sustained PRGT. The PRGT's potential self-sustained capacity is discussed in the context of longer-term projections of the demand for concessional lending.